Investigating The Extent of Cognitive Processes in Reading Skills Among Students at Suntisart School, Thailand - Lutfiah, Yuni; Arjulayana, Arjulayana; Hanim, Imtihan; Garba, Malami Muhammad (Jurnal Paedagogy, 2025)
This study aims to explore the cognitive processes involved in reading text english and examine the factors influencing high school students’ reading strategies at Suntisart School Thailand.  A qualitative research approach was employed, involving semi-structured interviews, classroom observations, and a review of students' reading activities. The study focused on senior high school students, observing their performance in decoding, fluency, and comprehension tasks during reading sessions. Interviews were conducted to uncover the students' thinking patterns and strategies for tackling reading challenges text english.  The data collected from the interviews and classroom observations were analyzed using the Miles and Huberman framework, which includes data collection, data reduction, data presentation, and drawing conclusions. The results found that more proficient readers applied strategies such as summarizing, making inferences, and reflecting on the text, which contributed to their understanding and retention of information. Additionally, students who struggled with reading often relied on external support from teachers or peers to manage their cognitive processes. The study concludes that students' ability to regulate their cognitive strategies plays a crucial role in their reading success and suggests that a combination of self-regulation and external guidance is essential for improving reading skills.